A three-dimensional thiophene-annulated perylene bisimide as a fullerene-free acceptor for a high performance polymer solar cell with the highest PCE of 8.28% and a VOC over 1.0 V. Issue 5 (19th January 2018) - Luo, Zhenghui; Liu, Tao; Cheng, Wanli; Wu, Kailong; Xie, Dongjun; Huo, Lijun; Sun, Yanming; Yang, Chuluo
Abstract : PSCs based onBPT-S achieved the PCE of 8.28%, which is the highest value based on S-annulated PBIs acceptors so far. Abstract : A new propeller-shaped small-molecule acceptor ofBPT-S with S-annulated perylene bisimide (PBI) as peripheral groups was designed and synthesized. Compared to the unannulated counterpart (BPT ), BPT-S exhibits a blue-shift absorption spectrum, stronger absorption in the region of 400–510 nm, higher LUMO energy level and twisted molecular geometry. TheBPT-S -based device withPDBT-T1 as the donor achieved a power conversion efficiency (PCE) as high as 8.28% with an impressively high open-circuit voltage ( V OC ) of 1.02 V, a near 16% enhancement in PCE with respect to theBPT -based control device (7.16%). The high photovoltaic performance for theBPT-S -based device can be attributed to its relatively high-lying LUMO level, complementary absorption spectra with the donor material, favorable morphology and balanced carrier transport. To the best of our knowledge, a PCE of 8.28% is the highest value for the device based on S-annulated PBIs as acceptors reported so far. This work indicates the great potential of the 3D S-annulated PBI-based acceptors for tandem (or multi-junction) organic solar cells due to the proper absorption spectra and high photovoltaic performance.